A Textbook Evaluation of “My Next Words” Grade 1: A Qualitative Content Analysis Using Tomlinson’s Framework - Defi Ela Safitri; Nur Lutfiah; Rahmahdalena Putri Khairunnisa (Journal Of Foreign Language Learning and Teaching, 2025)
Teaching materials serve as a bridge that connects theory and practice in language learning. In other words, teaching materials are created by prioritizing the developers' belief in effective language acquisition methods, which rely on targeted exposure and activities. This study aims to evaluate the content of the English textbook for grade 1 elementary school entitled "My Next Words Grade 1: Student's Book for Elementary School" using the teaching material evaluation framework from Tomlinson. Textbook evaluation is essential to ensure that the material delivered is appropriate to the needs and characteristics of the students. In this study, we will analyze the content of textbooks qualitatively to identify the strengths and weaknesses of the existing material. The method used is qualitative content analysis, focusing on aspects such as materials, presentations, and exercises contained in textbooks. The results of the analysis revealed that this book offers the use of contextual and repetitive vocabulary, multimodal support, and interactive classroom activities. All of this contributes to increased language retention and student learning independence. This book still has limitations in terms of integrating authentic texts and developing critical thinking skills. Although My Next Words has met several criteria for effective language teaching materials for beginners, it is recommended that further development be undertaken to balance communicative competencies with cognitive challenges. These results show that the application of the Tomlinson framework can improve the teaching quality as well as the practicality of textbooks used in learning English at the primary education level. The textbook "My Next Words" shows good potential as an English teaching material for grade 1 elementary school. However, some improvements and adjustments are needed to improve the overall quality.